Moral Character Education via Social Media: Youth in Urban Bandung Mosques - Kodir, Abdul; Syafei, Isop (FISIP UIN SGD Bandung, 2026)
Social media increasingly shapes urban youth's moral development, including mosque youth expected to model religious values—a challenge prior character education efforts, focused on cognitive and ritual aspects, have failed to address amid digital advances. Adolescents struggle to filter information, resist negative content, and sustain moral behavior online and offline. This study innovates by empowering mosque youth as moral agents blending religious values with digital literacy. Objectives include describing social media's moral impacts, evaluating character education's role, and assessing mosque-based community service in Bandung. Using qualitative case studies of three mosque youth groups (via observation, interviews, and documentation), findings reveal social media's ambivalent effects: bolstering religious identity yet risking degradation. Mosque-rooted programs effectively build moral literacy, self-control, and value-based networks, underscoring adaptive, community-driven models for youth morality in the social media era.